Complex Regional Pain Syndrome with Aortic Distress after Thoracic Endovascular Aortic Repair and False Lumen Exclusion with “Candy Plug” Technique - Tolva, Valerio S.; Kahlberg, Andrea; Bertoglio, Luca; Trimarchi, Santi; Miloro, Riccardo; Casana, Renato; Chiesa, Roberto (AORTA, 2021)
A 41-year-old male presented for pain treated with oxycodone. A zone-2 thoracic endovascular aortic repair with distal PETTICOAT (provisional extension to induce complete attachment) for complicated Type-IIIB aortic dissection was performed 18 months before. Repeated hospitalizations did not show any issues to justify the recurrent pain. The aortic nature of the pain was suspected considering the plug as a pain trigger. Through a left thoracoabdominal incision in the eighth intercostal space, the candy plug was removed. Pain diminished after thoracoabdominal surgery steadily.
Keywords: aortic dissection; TEVAR; aortic pain; acute aortic syndrome; candy plug; spinal cord protection; visceral perfusion